The Wzz (Cld) Protein in Escherichia coli: Amino Acid Sequence Variation Determines O-Antigen Chain Length Specificity - Franco, Agustin V. (American Society for Microbiology, 1998)
The O antigen is a polymer with a repeated unit. The chain length in most Escherichia coli strains has a modal value of 10 to 18 O units, but other strains have higher or lower modal values. wzz (cld/rol) mutants have a random chain length distribution, showing that the modal distribution is determined by the Wzz protein. Cloned wzz genes from E. coli strains with short (7 to 16), intermediate (10 to 18), and long (16 to 25) modal chain lengths were transferred to a model system, and their effects on O111 antigen were studied. The O111 chain length closely resembled that of the parent strains. We present data based on the construction of chimeric wzz genes and site-directed mutagenesis of the wzz gene to show that the modal value of O-antigen chain length of E. coli O1, O2, O7, and O157 strains can be changed by specific amino acid substitutions in wzz. It is concluded that the O-antigen chain length heterogeneity in E. coli strains is the result of amino acid sequence variation of the Wzz protein.